2023
DOI: 10.3390/pr11040974
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of the Use of Biodiesel Production from Essential Oils as Biofuels

Abstract: Second-generation biodiesel, which is produced from essential oil plants, has important advantages, including a high yield of biofuels and the potential to reduce greenhouse gas emissions. The goal of this research was to examine the profile of original and review articles on biodiesel production from essential oils using bibliometric analysis. The search strategy identified 186 relevant and available peer-reviewed publications from 1981 to 2023, which were downloaded from the Web of Science (WoS) database. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…The keyword cluster analysis revealed 10 main research topics, including biodiesel production from essential oils, diesel, fuel, and engine performance, and green chemistry. The study comes to the conclusion that in the drive for a sustainable and clean environment, subjects including various biodiesel raw material sources, biodiesel conversion technology, and the performance and emission characteristics of second-generation biodiesel are growing in popularity [26]. The findings demonstrated that adding clove oil at various volume percentages reduced fuel use, with 0.5% of clove oil causing the greatest decrease.…”
Section: Introductionmentioning
confidence: 97%
“…The keyword cluster analysis revealed 10 main research topics, including biodiesel production from essential oils, diesel, fuel, and engine performance, and green chemistry. The study comes to the conclusion that in the drive for a sustainable and clean environment, subjects including various biodiesel raw material sources, biodiesel conversion technology, and the performance and emission characteristics of second-generation biodiesel are growing in popularity [26]. The findings demonstrated that adding clove oil at various volume percentages reduced fuel use, with 0.5% of clove oil causing the greatest decrease.…”
Section: Introductionmentioning
confidence: 97%
“…Frying oils, vegetable oils, animal fats, and oil created by microorganisms can all be used to make biodiesel [3,4]. However, there are a number of benefits to using secondgeneration biodiesel made from essential oil plants, such as its ability to facilitate high biofuel production and to lower greenhouse gas emissions [5]. The first stage in the manufacturing of biodiesel, however, is the selection of the feedstock, which requires the consideration of a number of attributes, including the composition, purity of the fuel, yield, and cost.…”
Section: Introductionmentioning
confidence: 99%